A Nomogram for Predicting Non-Rebound in HBV-Infected Pregnant Women With Mother-to-Child Transmission Prevention - Wang, Chun-Rui; Zhong, Guo-Chao; Chen, Zhi-Wei; Hu, Peng (Frontiers in Medicine, 2021)
Abstract Background: Current guidelines recommend that pregnancies with mother-to-child transmission (MTCT) prevention can cease antiviral treatment after delivery. We aimed to develop a nomogram for predicting non-rebound in HBV-infected pregnant women with MTCT prevention after postpartum nucleos(t)ide analogues (NAs) withdrawal based on parameters before treatment cessation. Methods: Pregnant women receiving antiviral therapy for MTCT prevention who withdrew from taking NAs after delivery were included in this study. We used the least absolute shrinkage and selection operator logistics and two-way stepwise regression to select prognostic factors for the risk model, and the concordance index was used to assess its discrimination. Internal validation was performed through bootstrapping. Results: Of 92 included patients, 16 and 76 experienced non-rebound and virologic rebound within 48 weeks of postpartum NAs cessation, respectively. Platelet to lymphocyte ratio at 34 ± 2 weeks of gestation, reduction in hepatitis B surface antigen, from baseline to 34 ± 2 weeks of gestation, and hepatitis B virus DNA decline from baseline to end of treatment were entered into the final risk model. Its concordance index was 0.91 (95% confidence interval, 0.82–0.99) and reached as high as 0.88 after bootstrapping validation. The decision curve and decision tree were further developed to facilitate the application of this model. Conclusions: We developed a nomogram for predicting non-rebound in pregnant women with MTCT prevention after withdrawal of antiviral agents, which facilitates physicians in making appropriate treatment recommendations.